Volume 3: Coal, Biomass, Hydrogen, and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration; Organ 2019
DOI: 10.1115/gt2019-91541
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Combined Cycle Exploiting Inlet Conditioning Technologies for Power Modulation

Abstract: The high share of non-dispatchable renewable energy source generators in the electrical grid has increased the need for flexibility of Gas Turbine Combined Cycles (GTCC) already installed. To maximize not only the maximum power produced, via Power Augmentation Technologies (PATs), but also to reduce the Minimum Environmental Load (MEL), both OEMs and GTCC owners have adopted several technical solutions. This kind of flexibility has become, year-by-year, ever more crucial to guarantee GTCC economical sustainabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…More in detail, from an economic perspective the main difference between the ICU-CCGT integration and the other storage technologies relies on the value at which the discharging power is awarded. The thermal energy discharged by the TES is reflected in an extra power output of the CCGT and a slight variation in efficiency since the fuel consumption increases as well, a detailed investigation of the dependence on the ambient temperature and the GT load is provided in [35]. Thus the economic value of the discharged energy is the power increment, due to inlet cooling by TES discharging, times the Clean Spark Spread (CSS), i.e., the profit margin of a CCGT power plant considering the fuel consumption and the cost of carbon dioxide allowance emissions, equation (18).…”
Section: Icu-ccgt Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…More in detail, from an economic perspective the main difference between the ICU-CCGT integration and the other storage technologies relies on the value at which the discharging power is awarded. The thermal energy discharged by the TES is reflected in an extra power output of the CCGT and a slight variation in efficiency since the fuel consumption increases as well, a detailed investigation of the dependence on the ambient temperature and the GT load is provided in [35]. Thus the economic value of the discharged energy is the power increment, due to inlet cooling by TES discharging, times the Clean Spark Spread (CSS), i.e., the profit margin of a CCGT power plant considering the fuel consumption and the cost of carbon dioxide allowance emissions, equation (18).…”
Section: Icu-ccgt Comparisonmentioning
confidence: 99%
“…The ICU could work i) continuously, employing the HP to conditionate the CCGT intake, ii) as equivalent energy storage indeed using cheap electricity to drive the HP and charge the cold TES and using it to cool down the CCGT intake and boost the power output during the price peak periods without additional auxiliary losses. Preliminary works assessed the impact of intake temperature on the CCGT performance to investigate the potentialities of an ICU integration [35]. Subsequently, by means of a Mixed Integer Linear Programming (MILP) approach, it was developed a methodology to optimize the scheduling of an integrated ICU-CCGT power plant on the day-ahead market only [36] or considering the potentialities from an ancillary services provision [37].…”
Section: Introductionmentioning
confidence: 99%
“…(3)-( 5) are used to determine the initial condition of the iterative procedure solving the nonlinear system composed by Eqs. ( 6)- (8).…”
Section: -Heat Exchangersmentioning
confidence: 99%
“…The theoretical analysis by Sorce et al [8] highlighted the potential of this solution, showing an expected maximum power increase of +14% during TES discharge, a minimum environmental load reduction of -16% and an average efficiency increase of about +1% percentage points during offdesign operation. The study by Vannoni et al [9] showed that the butane-based HP can be particularly interesting for integration with new or existing GTCCs with an heat demand in the 80-150°C range, as well as for other power-to-heat solutions.…”
Section: -Introductionmentioning
confidence: 99%
“…In order to investigate the limits and potentialities of the two layouts of Case1, a MATLAB model was developed for the heat exchangers, the condensing process and the heat pump. For the rest of the combined cycle, data already available obtained via GateCycle has been used [5].…”
Section: Mathematical Modelsmentioning
confidence: 99%